Acceptability of a community cardiovascular disease prevention programme in Mukono and Buikwe districts in Uganda: a qualitative study - Rawlance Ndejjo; Geofrey Musinguzi; Fred Nuwaha; Rhoda K. Wanyenze; Hilde Bastiaens (BMC, 2020)
Abstract Background Cardiovascular diseases (CVDs) are on the rise in many low-and middle-income countries where 80% of related deaths are registered. Community CVD prevention programmes utilizing self-care approaches have shown promise in contributing to population level reduction of risk factors. However, the acceptability of these programmes, which affects their uptake and effectiveness, is unknown including in the sub-Saharan Africa context. This study used the Theoretical Framework of Acceptability to explore the prospective acceptability of a community CVD prevention programme in Mukono and Buikwe districts in Uganda. Methods This qualitative descriptive study was conducted in March 2019 among community health workers (CHWs), who would implement the intervention and community members, the intervention recipients, using eight focus group discussions. All discussions were audio-recorded, transcribed verbatim and analysed thematically guided by the theoretical framework. Results CHWs and community members reported high eagerness to participate in the programme. Whereas CHWs had implemented similar community programmes and cited health promotion as their role, community members looked forward to health services being brought nearer to them. Although the intervention was preventive in nature, CHWs and community members expressed high interest in treatments for risk factors and were skeptical about the health system capacity to deliver them. CHWs anticipated barriers in mobilising communities who they said sometimes may not be cooperative while community members were concerned about failing to access treatment and support services after screening for risk factors. The major cost to CHWs and community members for engaging in the intervention was time that they would have dedicated to income generating activities and social events though CHWs also had the extra burden of being exemplary. CHWs were confident in their ability to deliver the intervention as prescribed if well trained, supported and supervised, and community members felt that if provided sufficient information and supported by CHWs, they could change their behaviours. Conclusions The community CVD prevention programme was highly acceptable among CHWs and community members in Mukono and Buikwe districts of Uganda amidst a few burdens and opportunity costs. Suggestions made by study participants to improve programme effectiveness informed programme design and implementation for impact.